FRI0433 Nuclear Receptor NR4A1 as a Checkpoint of Physiological Wound Healing and Fibrosis. (9th June 2015) - Palumbo-Zerr, K.; Zerr, P.; Distler, A.; Mancuso, R.; Huang, J.; Tomcik, M.; Scholtysek, C.; Dees, C.; Beyer, C.; Krönke, G.; Distler, O.; Schett, G.; et al.
Abstract : Background: Nuclear receptor 4A1 (NR4A1) is a nuclear receptor without endogenous ligand. NR4A1 has pleiotropic regulatory effects on proliferation, differentiation and apoptosis. Deregulation of NR4A1 has been implication in the pathogenesis of cancer, metabolic, vascular and inflammatory diseases. Objectives: Here, we aimed to characterize the role of NR4A1 in physiologic and pathologic tissue responses and TGF-β signaling. Methods: Samples from various fibrotic diseases (SSc, IPF, liver and renal fibrosis, cGvHD) and experimental models of fibrosis were analyzed. The expression and molecular regulation of NR4A1 was analyzed by real-time PCR, Western Blot, immunofluorescence, IHC, siRNA mediated knockdown, CoIP, ChIP and reporter assays. Results: We characterized NR4A1 as an endogenous inhibitor of TGF-β signaling. Overexpression of NR4A1 in cultured fibroblasts prevented the pro-fibrotic effects of TGF-β, whereas knockdown of NR4A1 enhanced the sensitivity towards TGF-β. Similar results were obtained in vivo and conditional inactivation of Nr4a1 in fibroblasts exacerbated fibrosis in various models of skin and pulmonary fibrosis. NR4A1 regulated the expression of TGF-β target genes by SP1-dependent transrepression. Consistent with its anti-fibrotic effects, the levels of active NR4A1 were decreased in patients with SSc, IPF, liver fibrosis and cGvHD and respective mouse models. Mechanistically, chronic activation of TGF-β signaling in fibrotic diseases inactivates NR4A1 by HDAC-mediated epigenetic silencing and AKT-induced phosphorylation. Phosphorylated and thus inactivated NR4A1 accumulates in fibrotic disorders with decreased ratios of active to inactive NR4A1 in fibrotic diseases as compared to non-wounded tissue samples and to physiologic tissue responses during normal wound healing. Csn-B, a selective pharmacological agonist of NR4A1, prevented the inactivation of NR4A1 in fibrotic conditions. Treatment with Csn-B exerted potent anti-fibrotic effects and abrogated the profibrotic effects of TGF-β on cultured fibroblasts. Moreover, Csn-B ameliorated fibrosis in various models of dermal, pulmonary, renal and hepatic fibrosis in preventive and treatment dosing. Conclusions: NR4A1 is a key-checkpoint for mesenchymal tissue responses that limits TGF-β during normal wound healing. In fibrosis, however, chronically activated TGF-β signaling inactivates the NR4A1 feedback loop thus promoting persistent TGF-β signaling and chronic tissue remodeling. Small molecule agonists of NR4A1 can restore the regulatory activity of NR4A1, limit TGF-β signaling and inhibit fibrosis. Disclosure of Interest: None declared